PUBLICATIONS OF THE WEEK. (Bookseller, 2003)
Presents a list of books published this year, as of July 25, 2003. 'Radical Landscapes: Reinventing Outdoor Space,' by Jane Amidon; 'Clemente: A Retrospective,' by Lisa Dennison; 'Whispering Giant: The Story of the Bristol Britannia,' by F.R. McKim; 'Surveying With Construction Applications,' by Barry F. Kavanagh.